If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x-2=3(-x+2)
We move all terms to the left:
-3x-2-(3(-x+2))=0
We add all the numbers together, and all the variables
-3x-(3(-1x+2))-2=0
We calculate terms in parentheses: -(3(-1x+2)), so:We get rid of parentheses
3(-1x+2)
We multiply parentheses
-3x+6
Back to the equation:
-(-3x+6)
-3x+3x-6-2=0
We add all the numbers together, and all the variables
-8!=0
There is no solution for this equation
| -7(6k+7)+7=6k-42 | | 15=7+n+14 | | -42=-4k+3(-3k-1) | | -1x-2=3(-x+2) | | 5(x–6)+8-2x=x+2(x-11) | | 2x-(8x+1)=3x-19 | | 7-2n/3=5 | | -4x-11=-x+14+-3x | | -4x-11=-x+14+3x | | -6y+-45y=7.5-22.5 | | (3x/4)=90 | | -4x-11=-x+14+-4x | | 3x-9=4x-18 | | -8(5+6m)=36-10m | | 3x–7=2x+21 | | -6=4z-3 | | 10(4x-2)=-8x+28 | | (5x+6)2=3-(4x+12) | | 6-n/8=-19 | | 3.2+10m=6.17 | | 4x-19=8x-14 | | 4x+9=5x+4-x | | F(-2)=4x^2+2x-4 | | x^2+14x+24=180 | | 4x+9=5x+-5-x | | -(x-6)=46-9x | | –9k=–10k−10 | | 9r+8=10r | | -9+8h=9h | | 5x-1=X,6 | | 10z-15=20z | | -7+5n=-7(1+10n) |